open import Cat.Functor.Adjoint.Compose
open import Cat.Functor.Naturality
open import Cat.Functor.Properties
open import Cat.Functor.Adjoint
open import Cat.Functor.Base
open import Cat.Prelude

import Cat.Functor.Reasoning as Fr
import Cat.Reasoning

module Cat.Functor.Equivalence where

Equivalences🔗

A functor F:C→DF : \mathcal{C} \to \mathcal{D} is an equivalence of categories when it has a right adjoint G:D→DG : \mathcal{D} \to \mathcal{D}, with the unit and counit natural transformations being natural isomorphisms. This immediately implies that our adjoint pair F⊣GF \dashv G extends to an adjoint triple F⊣G⊣FF \dashv G \dashv F.

record is-equivalence (F : Functor C D) : Type (adj-level C D) where
  private
    module C = Cat.Reasoning C
    module D = Cat.Reasoning D
    module [C,C] = Cat.Reasoning Cat[ C , C ]
    module [D,D] = Cat.Reasoning Cat[ D , D ]

  field
    F⁻¹      : Functor D C
    F⊣F⁻¹    : F ⊣ F⁻¹

  open _⊣_ F⊣F⁻¹ public

  field
    unit-iso   : ∀ x → C.is-invertible (unit.η x)
    counit-iso : ∀ x → D.is-invertible (counit.ε x)

The first thing we note is that having a natural family of invertible morphisms gives isomorphisms in the respective functor categories:

  F∘F⁻¹≅Id : (F F∘ F⁻¹) [D,D].≅ Id
  F∘F⁻¹≅Id =
    [D,D].invertible→iso counit
      (invertible→invertibleⁿ _ counit-iso)

  Id≅F⁻¹∘F : Id [C,C].≅ (F⁻¹ F∘ F)
  Id≅F⁻¹∘F =
    [C,C].invertible→iso unit
      (invertible→invertibleⁿ _ unit-iso)

  unit⁻¹ = [C,C]._≅_.from Id≅F⁻¹∘F
  counit⁻¹ = [D,D]._≅_.from F∘F⁻¹≅Id
  F⁻¹⊣F : F⁻¹ ⊣ F
  F⁻¹⊣F = adj′ where
    module adj = _⊣_ F⊣F⁻¹
    open _⊣_
    adj′ : F⁻¹ ⊣ F
    adj′ .unit   = counit⁻¹
    adj′ .counit = unit⁻¹
    adj′ .zig {a} = zig′ where abstract
      p : η unit⁻¹ (F₀ F⁻¹ a) ≡ F₁ F⁻¹ (adj.counit.ε _)
      p =
        η unit⁻¹ (F₀ F⁻¹ a)                                                ≡⟨ C.introl adj.zag ⟩≡
        (F₁ F⁻¹ (adj.counit.ε _) C.∘ adj.unit.η _) C.∘ η unit⁻¹ (F₀ F⁻¹ a) ≡⟨ C.cancelr (unit-iso _ .C.is-invertible.invl) ⟩≡
        F₁ F⁻¹ (adj.counit.ε _)                                            ∎

      zig′ : η unit⁻¹ (F₀ F⁻¹ a) C.∘ F⁻¹ .F₁ (counit⁻¹ .η a) ≡ C.id
      zig′ = ap₂ C._∘_ p refl
        ·· sym (F-∘ F⁻¹ _ _)
        ·· ap (F₁ F⁻¹) (counit-iso _ .D.is-invertible.invl) ∙ F-id F⁻¹

    adj′ .zag {b} = zag′ where abstract
      p : counit⁻¹ .η (F₀ F b) ≡ F .F₁ (adj.unit.η b)
      p =
        counit⁻¹ .η _                                                     ≡⟨ D.intror adj.zig ⟩≡
        counit⁻¹ .η _ D.∘ adj.counit.ε (F₀ F b) D.∘ (F₁ F (adj.unit.η b)) ≡⟨ D.cancell (counit-iso _ .D.is-invertible.invr) ⟩≡
        F .F₁ (adj.unit.η b)                                              ∎

      zag′ : F .F₁ (unit⁻¹ .η b) D.∘ counit⁻¹ .η (F₀ F b) ≡ D.id
      zag′ = ap₂ D._∘_ refl p
        ·· sym (F .F-∘ _ _)
        ·· (ap (F .F₁) (unit-iso _ .C.is-invertible.invr) ∙ F .F-id)

  inverse-equivalence : is-equivalence F⁻¹
  inverse-equivalence =
    record { F⁻¹ = F ; F⊣F⁻¹ = F⁻¹⊣F
           ; unit-iso   = λ x → D.is-invertible-inverse (counit-iso _)
           ; counit-iso = λ x → C.is-invertible-inverse (unit-iso _)
           }

We chose, for definiteness, the above definition of equivalence of categories, since it provides convenient access to the most useful data: The induced natural isomorphisms, the adjunction unit/counit, and the triangle identities. It is a lot of data to come up with by hand, though, so we provide some alternatives:

Fully faithful, essentially surjective🔗

Any fully faithful and (split!) essentially surjective functor determines an equivalence of precategories. Recall that “split essentially surjective” means we have some determined procedure for picking out an essential fibre over any object d:Dd : \mathcal{D}: an object F∗(d):CF^*(d) : \mathcal{C} together with a specified isomorphism F∗(d)≅dF^*(d) \cong d.

module _ {F : Functor C D} (ff : is-fully-faithful F) (eso : is-split-eso F) where
  import Cat.Reasoning C as C
  import Cat.Reasoning D as D
  private module di = D._≅_

  private
    ff⁻¹ : ∀ {x y} → D.Hom (F .F₀ x) (F .F₀ y) → C.Hom _ _
    ff⁻¹ = equiv→inverse ff
    module ff {x} {y} = Equiv (_ , ff {x} {y})

It remains to show that, when FF is fully faithful, this assignment of essential fibres extends to a functor D→C\mathcal{D} \to \mathcal{C}. For the object part, we send xx to the specified preimage. For the morphism part, the splitting gives us isomorphisms F∗(x)≅xF^*(x) \cong x and F∗(y)≅yF^*(y) \cong y, so that we may form the composite F∗(x)→x→y→F∗(y)F^*(x) \to x \to y \to F^*(y); Fullness then completes the construction.

  ff+split-eso→inverse : Functor D C
  ff+split-eso→inverse .F₀ x         = eso x .fst
  ff+split-eso→inverse .F₁ {x} {y} f =
    ff⁻¹ (f*y-iso .D._≅_.from D.∘ f D.∘ f*x-iso .D._≅_.to)
    where
      open Σ (eso x) renaming (fst to f*x ; snd to f*x-iso)
      open Σ (eso y) renaming (fst to f*y ; snd to f*y-iso)
We must then, as usual, prove that this definition preserves identities and distributes over composites, so that we really have a functor. Preservation of identities is immediate; Distribution over composites is by faithfulness.
  ff+split-eso→inverse .F-id {x} =
    ff⁻¹ (f*x-iso .di.from D.∘ ⌜ D.id D.∘ f*x-iso .di.to ⌝) ≡⟨ ap! (D.idl _) ⟩≡
    ff⁻¹ (f*x-iso .di.from D.∘ f*x-iso .di.to)              ≡⟨ ap ff⁻¹ (f*x-iso .di.invr) ⟩≡
    ff⁻¹ D.id                                               ≡˘⟨ ap ff⁻¹ (F-id F) ⟩≡˘
    ff⁻¹ (F₁ F C.id)                                        ≡⟨ ff.η _ ⟩≡
    C.id                                                    ∎
    where open Σ (eso x) renaming (fst to f*x ; snd to f*x-iso)

  ff+split-eso→inverse .F-∘ {x} {y} {z} f g =
    fully-faithful→faithful {F = F} ff (
      F₁ F (ff⁻¹ (ffz D.∘ (f D.∘ g) D.∘ ftx))      ≡⟨ ff.ε _ ⟩≡
      ffz D.∘ (f D.∘ g) D.∘ ftx                    ≡⟨ cat! D ⟩≡
      ffz D.∘ f D.∘ ⌜ D.id ⌝ D.∘ g D.∘ ftx         ≡˘⟨ ap¡ (f*y-iso .di.invl) ⟩≡˘
      ffz D.∘ f D.∘ (fty D.∘ ffy) D.∘ g D.∘ ftx    ≡⟨ cat! D ⟩≡
      (ffz D.∘ f D.∘ fty) D.∘ (ffy D.∘ g D.∘ ftx)  ≡˘⟨ ap₂ D._∘_ (ff.ε _) (ff.ε _) ⟩≡˘
      F₁ F (ff⁻¹ _) D.∘ F₁ F (ff⁻¹ _)              ≡˘⟨ F-∘ F _ _ ⟩≡˘
      F₁ F (ff⁻¹ _ C.∘ ff⁻¹ _)                     ∎
    )
    where
      open Σ (eso x) renaming (fst to f*x ; snd to f*x-iso)
      open Σ (eso y) renaming (fst to f*y ; snd to f*y-iso)
      open Σ (eso z) renaming (fst to f*z ; snd to f*z-iso)

      ffz = f*z-iso .di.from
      ftz = f*z-iso .di.to
      ffy = f*y-iso .di.from
      fty = f*y-iso .di.to
      ffx = f*x-iso .di.from
      ftx = f*x-iso .di.to

We will, for brevity, refer to the functor we’ve just built as GG, rather than its “proper name” ff+split-eso→inverse. Hercules now only has 11 labours to go: We must construct unit and counit natural transformations, prove that they satisfy the triangle identities, and prove that the unit/counit we define are componentwise invertible. I’ll keep the proofs of naturality in <details> tags since.. they’re rough.

  private
    G = ff+split-eso→inverse

For the unit, we have an object x:Cx : \mathcal{C} and we’re asked to provide a morphism x→F∗F(x)x \to F^*F(x) — where, recall, the notation F∗(x)F^*(x) represents the chosen essential fibre of FF over xx. By fullness, it suffices to provide a morphism F(x)→FF∗F(x)F(x) \to FF^*F(x); But recall that the essential fibre F∗F(x)F^*F(x) comes equipped with an isomorphism FF∗F(x)≅F(x)FF^*F(x) \cong F(x).

  ff+split-eso→unit : Id => (G F∘ F)
  ff+split-eso→unit .η x = ff⁻¹ (f*x-iso .di.from)
    where open Σ (eso (F₀ F x)) renaming (fst to f*x ; snd to f*x-iso)
Naturality of ff+split-eso→unit.
  ff+split-eso→unit .is-natural x y f =
    fully-faithful→faithful {F = F} ff (
      F₁ F (ff⁻¹ ffy C.∘ f)                                    ≡⟨ F-∘ F _ _ ⟩≡
      ⌜ F₁ F (ff⁻¹ ffy) ⌝ D.∘ F₁ F f                           ≡⟨ ap! (ff.ε _) ⟩≡
      ffy D.∘ ⌜ F₁ F f ⌝                                       ≡⟨ ap! (sym (D.idr _) ∙ ap (F₁ F f D.∘_) (sym (f*x-iso .di.invl))) ⟩≡
      ffy D.∘ F₁ F f D.∘ ftx D.∘ ffx                           ≡⟨ cat! D ⟩≡
      (ffy D.∘ F₁ F f D.∘ ftx) D.∘ ffx                         ≡˘⟨ ap₂ D._∘_ (ff.ε _) (ff.ε _) ⟩≡˘
      F₁ F (ff⁻¹ (ffy D.∘ F₁ F f D.∘ ftx)) D.∘ F₁ F (ff⁻¹ ffx) ≡˘⟨ F-∘ F _ _ ⟩≡˘
      F₁ F (ff⁻¹ (ffy D.∘ F₁ F f D.∘ ftx) C.∘ ff⁻¹ ffx)        ≡⟨⟩
      F₁ F (F₁ (G F∘ F) f C.∘ x→f*x)                           ∎
    )
    where
      open Σ (eso (F₀ F x)) renaming (fst to f*x ; snd to f*x-iso)
      open Σ (eso (F₀ F y)) renaming (fst to f*y ; snd to f*y-iso)

      ffy = f*y-iso .di.from
      fty = f*y-iso .di.to
      ffx = f*x-iso .di.from
      ftx = f*x-iso .di.to

      x→f*x : C.Hom x f*x
      x→f*x = ff⁻¹ (f*x-iso .di.from)

      y→f*y : C.Hom y f*y
      y→f*y = ff⁻¹ (f*y-iso .di.from)

For the counit, we have to provide a morphism FF∗(x)→xFF^*(x) \to x; We can again pick the given isomorphism.

  ff+split-eso→counit : (F F∘ G) => Id
  ff+split-eso→counit .η x = f*x-iso .di.to
    where open Σ (eso x) renaming (fst to f*x ; snd to f*x-iso)
Naturality of ff+split-eso→counit
  ff+split-eso→counit .is-natural x y f =
    fty D.∘ ⌜ F₁ F (ff⁻¹ (ffy D.∘ f D.∘ ftx)) ⌝ ≡⟨ ap! (ff.ε _) ⟩≡
    fty D.∘ ffy D.∘ f D.∘ ftx                   ≡⟨ D.cancell (f*y-iso .di.invl) ⟩≡
    f D.∘ ftx                                   ∎
    where
      open Σ (eso x) renaming (fst to f*x ; snd to f*x-iso)
      open Σ (eso y) renaming (fst to f*y ; snd to f*y-iso)

      ffy = f*y-iso .di.from
      fty = f*y-iso .di.to
      ftx = f*x-iso .di.to

Checking the triangle identities, and that the adjunction unit/counit defined above are natural isomorphisms, is routine. We present the calculations without commentary:

  open _⊣_

  ff+split-eso→F⊣inverse : F ⊣ G
  ff+split-eso→F⊣inverse .unit    = ff+split-eso→unit
  ff+split-eso→F⊣inverse .counit  = ff+split-eso→counit
  ff+split-eso→F⊣inverse .zig {x} =
    ftx D.∘ F₁ F (ff⁻¹ ffx) ≡⟨ ap (ftx D.∘_) (ff.ε _) ⟩≡
    ftx D.∘ ffx             ≡⟨ f*x-iso .di.invl ⟩≡
    D.id                    ∎

The zag identity needs an appeal to faithfulness:

  ff+split-eso→F⊣inverse .zag {x} =
    fully-faithful→faithful {F = F} ff (
      F₁ F (ff⁻¹ (ffx D.∘ ftx D.∘ fftx) C.∘ ff⁻¹ fffx)        ≡⟨ F-∘ F _ _ ⟩≡
      F₁ F (ff⁻¹ (ffx D.∘ ftx D.∘ fftx)) D.∘ F₁ F (ff⁻¹ fffx) ≡⟨ ap₂ D._∘_ (ff.ε _) (ff.ε _) ⟩≡
      (ffx D.∘ ftx D.∘ fftx) D.∘ fffx                         ≡⟨ cat! D ⟩≡
      (ffx D.∘ ftx) D.∘ (fftx D.∘ fffx)                       ≡⟨ ap₂ D._∘_ (f*x-iso .di.invr) (f*f*x-iso .di.invl) ⟩≡
      D.id D.∘ D.id                                           ≡⟨ D.idl _ ∙ sym (F-id F) ⟩≡
      F₁ F C.id                                               ∎
    )

Now to show they are componentwise invertible:

  open is-equivalence

  ff+split-eso→is-equivalence : is-equivalence F
  ff+split-eso→is-equivalence .F⁻¹ = G
  ff+split-eso→is-equivalence .F⊣F⁻¹ = ff+split-eso→F⊣inverse
  ff+split-eso→is-equivalence .counit-iso x = record
    { inv      = f*x-iso .di.from
    ; inverses = record
      { invl = f*x-iso .di.invl
      ; invr = f*x-iso .di.invr }
    }
    where open Σ (eso x) renaming (fst to f*x ; snd to f*x-iso)

Since the unit is defined in terms of fullness, showing it is invertible needs an appeal to faithfulness (two, actually):

  ff+split-eso→is-equivalence .unit-iso x = record
    { inv      = ff⁻¹ (f*x-iso .di.to)
    ; inverses = record
      { invl = fully-faithful→faithful {F = F} ff (
          F₁ F (ff⁻¹ ffx C.∘ ff⁻¹ ftx)        ≡⟨ F-∘ F _ _ ⟩≡
          F₁ F (ff⁻¹ ffx) D.∘ F₁ F (ff⁻¹ ftx) ≡⟨ ap₂ D._∘_ (ff.ε _) (ff.ε _) ⟩≡
          ffx D.∘ ftx                         ≡⟨ f*x-iso .di.invr ⟩≡
          D.id                                ≡˘⟨ F-id F ⟩≡˘
          F₁ F C.id                           ∎)
      ; invr = fully-faithful→faithful {F = F} ff (
          F₁ F (ff⁻¹ ftx C.∘ ff⁻¹ ffx)        ≡⟨ F-∘ F _ _ ⟩≡
          F₁ F (ff⁻¹ ftx) D.∘ F₁ F (ff⁻¹ ffx) ≡⟨ ap₂ D._∘_ (ff.ε _) (ff.ε _) ⟩≡
          ftx D.∘ ffx                         ≡⟨ f*x-iso .di.invl ⟩≡
          D.id                                ≡˘⟨ F-id F ⟩≡˘
          F₁ F C.id                           ∎)
      }
    }
    where
      open Σ (eso (F₀ F x)) renaming (fst to f*x ; snd to f*x-iso)
      ffx = f*x-iso .di.from
      ftx = f*x-iso .di.to

Between categories🔗

Above, we made an equivalence out of any fully faithful and split essentially surjective functor. In set-theoretic mathematics (and indeed between strict categories), the splitting condition can not be lifted constructively: the statement “every (ff, eso) functor between strict categories is an equivalence” is equivalent to the axiom of choice.

However, between univalent categories, the situation is different: Any essentially surjective fully faithful functor splits. In particular, any ff functor between univalent categories has propositional essential fibres, so a “mere” essential surjection is automatically split. However, note that both the domain and codomain have to be categories for the argument to go through.

module
  _ (F : Functor C D) (ccat : is-category C) (dcat : is-category D)
    (ff : is-fully-faithful F)
  where
  private
    module C = Cat.Reasoning C
    module D = Cat.Reasoning D

So, suppose we have categories C\mathcal{C} and D\mathcal{D}, together with a fully faithful functor F:C→DF : \mathcal{C} \to \mathcal{D}. For any y:Dy : \mathcal{D}, we’re given an inhabitant of ∥∑x:CF(x)≅y∥\| \sum_{x : \mathcal{C}} F(x) \cong y \|, which we want to “get out” from under the truncation. For this, we’ll show that the type being truncated is a proposition, so that we may “untruncate” it.

  Essential-fibre-between-cats-is-prop : ∀ y → is-prop (Essential-fibre F y)
  Essential-fibre-between-cats-is-prop z (x , i) (y , j) = they're-equal where

For this magic trick, assume we’re given a z:Dz : \mathcal{D}, together with objects x,y:Cx, y : \mathcal{C} and isomorphisms i:F(x)≅zi : F(x) \cong z and j:F(y)≅zj : F(y) \cong z. We must show that x≡yx \equiv y, and that over this path, i=ji = j. Since FF is fully faithful, we can find an isomorphism x≅yx \cong y in C\mathcal{C}, which FF sends back to i∘j−1i \circ j^{-1}.

    Fx≅Fy : F₀ F x D.≅ F₀ F y
    Fx≅Fy = i D.∘Iso (j D.Iso⁻¹)

    x≅y : x C.≅ y
    x≅y = is-ff→essentially-injective {F = F} ff Fx≅Fy

Furthermore, since we’re working with categories, these isomorphisms restrict to paths x≡yx \equiv y and F(x)≡F(y)F(x) \equiv F(y). We’re half-done: we’ve shown that some p:x≡yp : x \equiv y exists, and it remains to show that over this path we have i≡ji \equiv j. More specifically, we must give a path i≡ji \equiv j laying over ap⁡(F)(p)\operatorname{ap}(F)(p).

    x≡y : x ≡ y
    x≡y = ccat .to-path x≅y

    Fx≡Fy : F₀ F x ≡ F₀ F y
    Fx≡Fy = dcat .to-path Fx≅Fy

Rather than showing it over p:x≡yp : x\equiv y directly, we’ll show it over the path F(x)≡F(y)F(x) \equiv F(y) we constructed independently. This is because we can use the helper Hom-pathp-reflr-iso to establish the result with far less computation:

    over′ : PathP (λ i → Fx≡Fy i D.≅ z) i j
    over′ = D.≅-pathp Fx≡Fy refl
      (Univalent.Hom-pathp-refll-iso dcat (D.cancell (i .D._≅_.invl)))

We must then connect ap⁡(F)(p)\operatorname{ap}(F)(p) with this path F(x)≅F(y)F(x) \cong F(y). But since we originally got pp by full faithfulness of FF, they are indeed the same path:

    abstract
      square : ap (F₀ F) x≡y ≡ Fx≡Fy
      square =
        ap (F₀ F) x≡y                     ≡⟨ F-map-path ccat dcat F x≅y ⟩≡
        dcat .to-path ⌜ F-map-iso F x≅y ⌝ ≡⟨ ap! (equiv→counit (is-ff→F-map-iso-is-equiv {F = F} ff) _)  ⟩≡
        dcat .to-path Fx≅Fy               ∎

    over : PathP (λ i → F₀ F (x≡y i) D.≅ z) i j
    over = transport (λ l → PathP (λ m → square (~ l) m D.≅ z) i j) over′

Hence — blink and you’ll miss it — the essential fibres of FF over any z:Dz : \mathcal{D} are propositions, so it suffices for them to be merely inhabited for the functor to be split eso. With tongue firmly in cheek we call this result the theorem of choice.

    they're-equal = Σ-pathp x≡y over

  Theorem-of-choice : is-eso F → is-split-eso F
  Theorem-of-choice eso y =
    ∥-∥-elim (λ _ → Essential-fibre-between-cats-is-prop y)
      (λ x → x) (eso y)

This theorem implies that any fully faithful, “merely” essentially surjective functor between categories is an equivalence:

  ff+eso→is-equivalence : is-eso F → is-equivalence F
  ff+eso→is-equivalence eso = ff+split-eso→is-equivalence ff (Theorem-of-choice eso)

Furthermore, if F:C→DF : \mathcal{C} \to \mathcal{D} is an equivalence between categories, then it’s an equivalence-on-objects functor. The inverse functor F−1:D→CF^{-1} : \mathcal{D} \to \mathcal{C} gives us a way to turn objects of D\mathcal{D} back into objects of C\mathcal{C}, and unit/counit of the equivalence ensure that c≅F−1(F(c))c \cong F^{-1}(F(c)) and d≅F(F−1(d))d \cong F(F^{-1}(d)), so all that remains is to use the fact that C\mathcal{C} and D\mathcal{D} are categories to get the requisite paths.

is-cat-equivalence→equiv-on-objects
  : ∀ {F : Functor C D}
  → (ccat : is-category C) (dcat : is-category D)
  → is-equivalence F → is-equiv-on-objects F
is-cat-equivalence→equiv-on-objects {C = C} {D = D} {F = F} ccat dcat eqv =
  is-iso→is-equiv $
    iso (e.F⁻¹ .F₀)
      (λ d → dcat .to-path (D.invertible→iso _ (e.counit-iso d)))
      (λ c → sym $ ccat .to-path (C.invertible→iso _ (e.unit-iso c)))
  where
    module C = Cat.Reasoning C
    module D = Cat.Reasoning D
    module e = is-equivalence eqv

Isomorphisms🔗

Another, more direct way of proving that a functor is an equivalence of precategories is proving that it is an isomorphism of precategories: It’s fully faithful, thus a typal equivalence of morphisms, and in addition its action on objects is an equivalence of types.

record is-precat-iso (F : Functor C D) : Type (adj-level C D) where
  no-eta-equality
  constructor iso
  field
    has-is-ff  : is-fully-faithful F
    has-is-iso : is-equiv (F₀ F)

Such a functor is (immediately) fully faithful, and the inverse has-is-iso means that it is split essentially surjective; For given y:Dy : D, the inverse of F0F_0 gives us an object F−1(y)F^{-1}(y); We must then provide an isomorphism F(F−1(y))≅yF(F^{-1}(y)) \cong y, but those are identical, hence isomorphic.

module _ {F : Functor C D} (p : is-precat-iso F) where
  open is-precat-iso p

  is-precat-iso→is-split-eso : is-split-eso F
  is-precat-iso→is-split-eso ob = equiv→inverse has-is-iso ob , isom
    where isom = path→iso {C = D} (equiv→counit has-is-iso _)

Thus, by the theorem above, FF is an adjoint equivalence of precategories.

  is-precat-iso→is-equivalence : is-equivalence F
  is-precat-iso→is-equivalence =
    ff+split-eso→is-equivalence has-is-ff is-precat-iso→is-split-eso
open is-equivalence
open Precategory
open _⊣_

Id-is-equivalence : ∀ {o h} {C : Precategory o h} → is-equivalence {C = C} Id
Id-is-equivalence {C = C} .F⁻¹ = Id
Id-is-equivalence {C = C} .F⊣F⁻¹ .unit .η x = C .id
Id-is-equivalence {C = C} .F⊣F⁻¹ .unit .is-natural x y f = C .idl _ ∙ sym (C .idr _)
Id-is-equivalence {C = C} .F⊣F⁻¹ .counit .η x = C .id
Id-is-equivalence {C = C} .F⊣F⁻¹ .counit .is-natural x y f = C .idl _ ∙ sym (C .idr _)
Id-is-equivalence {C = C} .F⊣F⁻¹ .zig = C .idl _
Id-is-equivalence {C = C} .F⊣F⁻¹ .zag = C .idl _
Id-is-equivalence {C = C} .unit-iso x =
  Cat.Reasoning.make-invertible C (C .id) (C .idl _) (C .idl _)
Id-is-equivalence {C = C} .counit-iso x =
  Cat.Reasoning.make-invertible C (C .id) (C .idl _) (C .idl _)

private unquoteDecl eqv = declare-record-iso eqv (quote is-precat-iso)
instance
  H-Level-is-precat-iso
    : ∀ {o h o′ h′} {C : Precategory o h} {D : Precategory o′ h′}
        {F : Functor C D} {n}
    → H-Level (is-precat-iso F) (suc n)
  H-Level-is-precat-iso = prop-instance (Iso→is-hlevel 1 eqv (hlevel 1))

module
  _ {o ℓ o′ ℓ′} {C : Precategory o ℓ} {D : Precategory o′ ℓ′}
    (F : Functor C D) (eqv : is-equivalence F)
  where
  private
    module e = is-equivalence eqv
    module C = Cat.Reasoning C
    module D = Cat.Reasoning D
    module F = Fr F

  is-equivalence→is-ff : is-fully-faithful F
  is-equivalence→is-ff = is-iso→is-equiv λ where
    .is-iso.inv x → e.unit⁻¹ .η _ C.∘ L-adjunct e.F⊣F⁻¹ x
    .is-iso.rinv x →
      D.invertible→monic (F-map-invertible F (e.unit-iso _)) _ _ $
        ap₂ D._∘_ refl (F .F-∘ _ _)
      ·· D.cancell (F.annihilate (e.unit-iso _ .C.is-invertible.invl))
      ·· D.invertible→monic (e.counit-iso _) _ _
          (R-L-adjunct e.F⊣F⁻¹ x ∙ sym (D.cancell e.zig))
    .is-iso.linv x →
        ap (_ C.∘_) (sym (e.unit .is-natural _ _ _))
      ∙ C.cancell (e.unit-iso _ .C.is-invertible.invr)

  is-equivalence→is-split-eso : is-split-eso F
  is-equivalence→is-split-eso y =
    (e.F⁻¹ .F₀ y) ,
    D.invertible→iso (e.counit .η y) (e.counit-iso y)

  is-equivalence→is-eso : is-eso F
  is-equivalence→is-eso y =
    inc ((e.F⁻¹ .F₀ y) , D.invertible→iso (e.counit .η y) (e.counit-iso y))

  open is-precat-iso
  open is-iso

  is-equivalence→is-precat-iso
    : is-category C → is-category D → is-precat-iso F
  is-equivalence→is-precat-iso c-cat d-cat .has-is-ff =
    is-equivalence→is-ff
  is-equivalence→is-precat-iso c-cat d-cat .has-is-iso =
    is-cat-equivalence→equiv-on-objects c-cat d-cat eqv

Properties of Equivalences🔗

If F:C→DF : \mathcal{C} \to \mathcal{D} is fully-faithfuly and essentially surjective, then for every hom-set D(d,d′)\mathcal{D}(d,d') there (merely) exists an equivalent hom-set C(c,c′)\mathcal{C}(c,c').

  ff+split-eso→hom-equiv
    : (F : Functor C D)
    → is-fully-faithful F
    → is-split-eso F
    → ∀ (d d' : D.Ob) → Σ[ c ∈ C.Ob ] Σ[ c' ∈ C.Ob ] (C.Hom c c' ≃ D.Hom d d')
  ff+split-eso→hom-equiv F ff split-eso d d' =
    d-fib .fst , d'-fib .fst ,
    (F .F₁ , ff) ∙e D.iso→hom-equiv (d-fib .snd) (d'-fib .snd)
    where
      d-fib = split-eso d
      d'-fib = split-eso d'

  ff+eso→hom-equiv
    : (F : Functor C D)
    → is-fully-faithful F
    → is-eso F
    → ∀ (d d' : D.Ob) → ∥ Σ[ c ∈ C.Ob ] Σ[ c' ∈ C.Ob ] (C.Hom c c' ≃ D.Hom d d') ∥
  ff+eso→hom-equiv F ff eso d d' = do
      (c , Fc≅d) ← eso d
      (c' , Fc'≅d') ← eso d'
      pure (c , c' , (F .F₁ , ff) ∙e D.iso→hom-equiv Fc≅d Fc'≅d')

This allows us to prove a very useful little lemma: if F:C→DF : \mathcal{C} \to \mathcal{D} is a fully-faithful, essentially surjective functor, then any property of hom-sets of C\mathcal{C} that holds for all hom-sets must also hold for all hom-sets of D\mathcal{D}.

  ff+eso→preserves-hom-props
    : ∀ {ℓ} (F : Functor C D)
    → is-fully-faithful F
    → is-eso F
    → (P : Type (ℓc ⊔ ℓd) → Type ℓ)
    → (∀ A → is-prop (P A))
    → (∀ c c' → P (Lift ℓd (C.Hom c c')))
    → ∀ d d' → P (Lift ℓc (D.Hom d d'))
  ff+eso→preserves-hom-props F ff eso P prop P-hom d d' =
    ∥-∥-proj {ap = prop (Lift ℓc (D.Hom d d'))} $ do
      (c , c' , eqv) ← ff+eso→hom-equiv F ff eso d d'
      pure (transport (ap P (ua (Lift-ap eqv))) (P-hom c c'))

As a corollary, we note that if F:C→DF : \mathcal{C} \to \mathcal{D} is a fully-faithful, essentially surjective functor, then if the hom-sets of C\mathcal{C} are all nn-types, then the hom-sets of D\mathcal{D} must also be nn-types.

  ff+eso→hom-hlevel
    : ∀ {n} (F : Functor C D)
    → is-fully-faithful F
    → is-eso F
    → (∀ c c' → is-hlevel (C.Hom c c') n)
    → ∀ d d' → is-hlevel (D.Hom d d') n
  ff+eso→hom-hlevel {n = n} F ff eso C-hlevel d d' =
    Lift-is-hlevel' _ $
    ff+eso→preserves-hom-props F ff eso
      (λ A → is-hlevel A n) (λ _ → is-hlevel-is-prop n)
      (λ c c' → Lift-is-hlevel n (C-hlevel c c')) d d'

Note that if FF is fully faithful and split essentially surjective, then we can drop the requirement that PP must be a prop.

  ff+split-eso→preserves-hom-fams
    : ∀ {ℓ} (F : Functor C D)
    → is-fully-faithful F
    → is-split-eso F
    → (P : Type (ℓc ⊔ ℓd) → Type ℓ)
    → (∀ c c' → P (Lift ℓd (C.Hom c c')))
    → ∀ d d' → P (Lift ℓc (D.Hom d d'))
  ff+split-eso→preserves-hom-fams F ff split-eso P P-hom d d' =
    transport
      (ap P (ua (Lift-ap (ff+split-eso→hom-equiv F ff split-eso d d' .snd .snd))))
      (P-hom _ _)

As a corollary, equivalences preserve all families over hom sets.

  equivalence→preserves-hom-fams
    : ∀ {ℓ} (E : Equivalence C D)
    → (P : Type (ℓc ⊔ ℓd) → Type ℓ)
    → (∀ c c' → P (Lift ℓd (C.Hom c c')))
    → ∀ d d' → P (Lift ℓc (D.Hom d d'))
  equivalence→preserves-hom-fams E =
    ff+split-eso→preserves-hom-fams (Equivalence.To E)
      (is-equivalence→is-ff _ (Equivalence.To-equiv E))
      (is-equivalence→is-split-eso _ (Equivalence.To-equiv E))

Being an equivalence is also invariant under natural isomorphism.

is-equivalence-natural-iso
  : ∀ {F G : Functor C D}
  → F ≅ⁿ G
  → is-equivalence F → is-equivalence G
is-equivalence-natural-iso {C = C} {D = D} {F = F} {G = G} α F-eqv = G-eqv where
  open is-equivalence
  module C = Cat.Reasoning C
  module D = Cat.Reasoning D

  G-eqv : is-equivalence G
  G-eqv .F⁻¹ = F-eqv .F⁻¹
  G-eqv .F⊣F⁻¹ = adjoint-natural-isol α (F-eqv .F⊣F⁻¹)
  G-eqv .unit-iso x =
    C.invertible-∘
      (C.invertible-∘
        (F-map-invertible (F-eqv .F⁻¹) (isoⁿ→is-invertible α x))
        C.id-invertible)
      (F-eqv .unit-iso x)
  G-eqv .counit-iso x =
    D.invertible-∘
      (F-eqv .counit-iso x)
      (D.invertible-∘
        (F-map-invertible F C.id-invertible)
        (isoⁿ→is-invertible α _ D.invertible⁻¹))

Equivalences are invertible.

_Equivalence⁻¹
  : Equivalence C D → Equivalence D C
(E Equivalence⁻¹) .Equivalence.To = Equivalence.From E
(E Equivalence⁻¹) .Equivalence.To-equiv = Equivalence.inverse-equivalence E

Equivalences are also composable, as adjoints compose.

is-equivalence-∘
  : ∀ {F : Functor D E} {G : Functor C D}
  → is-equivalence F → is-equivalence G
  → is-equivalence (F F∘ G)
is-equivalence-∘ {E = E} {C = C}  {F = F} {G = G} F-eqv G-eqv = FG-eqv where
  module F-eqv = is-equivalence F-eqv
  module G-eqv = is-equivalence G-eqv
  module C = Cat.Reasoning C
  module E = Cat.Reasoning E

  FG-eqv : is-equivalence (F F∘ G)
  FG-eqv .F⁻¹ = G-eqv.F⁻¹ F∘ F-eqv.F⁻¹
  FG-eqv .F⊣F⁻¹ = LF⊣GR G-eqv.F⊣F⁻¹ F-eqv.F⊣F⁻¹
  FG-eqv .unit-iso x =
    C.invertible-∘
      (F-map-invertible G-eqv.F⁻¹ (F-eqv.unit-iso (G .F₀ x)))
      (G-eqv.unit-iso x)
  FG-eqv .counit-iso x =
    E.invertible-∘
      (F-eqv.counit-iso x)
      (F-map-invertible F (G-eqv.counit-iso (F-eqv .F⁻¹ .F₀ x)))

_∘Equivalence_ : Equivalence C D → Equivalence D E → Equivalence C E
(F ∘Equivalence G) .Equivalence.To =
  Equivalence.To G F∘ Equivalence.To F
(F ∘Equivalence G) .Equivalence.To-equiv =
  is-equivalence-∘ (Equivalence.To-equiv G) (Equivalence.To-equiv F)